CSR, GCG and Company Size Impact on Profitability and Company Value - Risal; Agustan Syamsuddin; Sitti Murniati; Andi Nirwana Nur (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2025)
This research investigates the influence of CSR, GCG, and Company Size on the profitability and firm value of manufacturing companies listed on the Indonesia Stock Exchange. With a sample of 234 companies using purposive sampling, the study adopts a quantitative descriptive and explanatory approach, applying SEM for hypothesis testing. The results indicate a positive influence of CSR on firm value, while GCG and company size negatively affect profitability. Other findings include the negative impact of GCG and company size on firm value and the positive influence of CSR on firm value through profitability. The implication is that companies need to consider CSR, GCG, and company size in their strategies to enhance value and investment attractiveness.